2016
DOI: 10.1007/s00198-016-3802-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of Dickkopf-1 are indicative of Wnt/β-catenin downregulation and lower osteoblast signaling in children and adolescents with type 1 diabetes mellitus, contributing to lower bone mineral density

Abstract: Higher levels of Dickkopf-1 could indicate a downregulated Wnt/β-catenin system with possible lower osteoblast activation and higher osteoclast signaling in T1D children and adolescents. Dickkopf-1 could possibly be a significant contributor of T1D osteopathy. Future therapies could focus on Wnt/β-catenin metabolic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…T1DM is characterised as a state of low bone turnover [ 68 ], as determined by osteoblast dysfunction [ 65 67 ]. Of note is that insulin deficiency and insulin-like growth factor-1 (IGF-1) reduction [ 27 , 46 48 ] and hyperglycaemia-induced oxidative stress and accumulation of advanced glycation end-products (AGEs) that compromise collagen properties [ 69 , 70 ], low osteocalcin levels [ 62 , 63 ], and/or Wnt signalling pathway [ 71 , 72 ] seem to be causing these changes, resulting in a reduction in the mature osteoblast numbers and thus bone formation, leading to low peak bone mass at a young age [ 31 34 ]. Other factors such as inflammatory systemic diseases are characterised by increased levels of proinflammatory cytokines [ 73 ] that uncouple the bone remodelling cycle, also interfering with bone mass acquisition [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…T1DM is characterised as a state of low bone turnover [ 68 ], as determined by osteoblast dysfunction [ 65 67 ]. Of note is that insulin deficiency and insulin-like growth factor-1 (IGF-1) reduction [ 27 , 46 48 ] and hyperglycaemia-induced oxidative stress and accumulation of advanced glycation end-products (AGEs) that compromise collagen properties [ 69 , 70 ], low osteocalcin levels [ 62 , 63 ], and/or Wnt signalling pathway [ 71 , 72 ] seem to be causing these changes, resulting in a reduction in the mature osteoblast numbers and thus bone formation, leading to low peak bone mass at a young age [ 31 34 ]. Other factors such as inflammatory systemic diseases are characterised by increased levels of proinflammatory cytokines [ 73 ] that uncouple the bone remodelling cycle, also interfering with bone mass acquisition [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that osteoblasts in T1DM onset undergo transdifferentiation, dedifferentiation and cell death due to defects in the bone marrow stromal cell function . However, a plausible explanation for the reduced osteoblast function is evidenced by elevated levels of Dickkopf‐1 in T1DM, a known inhibitor of the Wnt/β‐catenin signalling pathway . The Wnt/β‐catenin signalling pathway regulates osteoblast differentiation and function whereby its downregulation in mice models has been correlated with reduced bone mineral density and increased frequency of osteocyte apoptosis .…”
Section: Bone Defects In Diabetic Patientsmentioning
confidence: 99%
“…[20] The Wnt/b-catenin signalling pathway regulates osteoblast differentiation and function whereby its downregulation in mice models has been correlated with reduced bone mineral density and increased frequency of osteocyte apoptosis. [20] In contrast, osteoclasts in type 1 diabetic mouse models demonstrated hypersensitivity to the effects of the RANKL, one of two major mediators of osteoclast differentiation with the second being the macrophage colony-stimulating factor. [21] Consequently, this causes extensive bone resorption via the upregulated expression of cathepsin K, matrix metalloproteinase-9 (MMP-9) and pro-osteoclast soluble mediators.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor γ (PPARγ) and the WNT/β-catenin pathway act in an opposite manner in many diseases, including MS [ 17 , 18 ]. Numerous autoimmune disorders present this opposed interplay, such as type 1 diabetes [ 19 , 20 ], thyroid autoimmunity [ 21 , 22 ] and rheumatoid arthritis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%